2020
DOI: 10.1128/jvi.02100-19
|View full text |Cite
|
Sign up to set email alerts
|

Ebola Virus Inclusion Body Formation and RNA Synthesis Are Controlled by a Novel Domain of Nucleoprotein Interacting with VP35

Abstract: Ebola virus (EBOV) inclusion bodies (IBs) are cytoplasmic sites of nucleocapsid formation and RNA replication, housing key steps in the virus life cycle that warrant further investigation. During infection IBs display dynamic properties regarding their size and location. Also, the contents of IBs must transition prior to further viral maturation, assembly and release, implying additional steps in IB function. Interestingly, expression of the viral nucleoprotein (NP) alone is sufficient for generation of IBs, i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 66 publications
4
27
0
Order By: Relevance
“…In the case of Borna disease virus (BDV, another member of the Mononegavirales order), the P protein alone is sufficient to sustain the formation of IBs with a probable liquid nature [184]. Likewise, the N protein from EBOV is sufficient for IB generation [185]. By contrast, in the case of VSV, co-expression of the L protein is required [180].…”
Section: Examples Of Viral Proteins Undergoing Llps Associated With Vmentioning
confidence: 99%
See 1 more Smart Citation
“…In the case of Borna disease virus (BDV, another member of the Mononegavirales order), the P protein alone is sufficient to sustain the formation of IBs with a probable liquid nature [184]. Likewise, the N protein from EBOV is sufficient for IB generation [185]. By contrast, in the case of VSV, co-expression of the L protein is required [180].…”
Section: Examples Of Viral Proteins Undergoing Llps Associated With Vmentioning
confidence: 99%
“…This is an interesting example of crosstalk between MLOs formed by LLPS and classical intracellular organelles [156,194]. The cytosolic puncta (i.e., the small, spherical condensates) form and dissolve reversibly and react promptly to changes in the chemical environment, such as hypotonic stress and addition of 1,6-hexanediol, a reagent known to perturb LLPS [185]. The viral inclusions can form even when only one type of RNP is expressed, thus revealing that their formation does not depend on RNA-RNA interactions among distinct ribonucleoproteins, as previously thought.…”
Section: Examples Of Viral Proteins Undergoing Llps Associated With Vmentioning
confidence: 99%
“…It was recently shown that the C-terminal domain of EBOV NP is necessary for IB formation and that co-expression of VP35 can rescue IB formation upon expression of a C-terminal deleted NP [166]. This experiment suggests that IB formation and other functions of NP and VP35 involved in transcription and replication of viral RNA are separated processes, since RNA synthesis could not be rescued in this setting.…”
Section: Filoviridae: Ibs Of Marv and Ebovmentioning
confidence: 97%
“…Several viruses similarly re-localize hnRNP C1/C2 to the cytoplasm, either for viral replication or IRES-dependent viral protein translation [99][100][101][102], which suggests that VP24-dependent hnRNP C1/C2 cytoplasmic accumulation is essential for EBOV replication [97]. Together, nucleoproteins (NPs) and VP35 form EBOV inclusion bodies (IBs) for viral replication [103]. A study conducted by Gabriel et al showed that importin-α7 is also involved in IB formation [104].…”
Section: Ebola Virus (Zaire Ebolavirus)mentioning
confidence: 99%